A description of the elevation of pericardial cortisol: cortisone ratio in patients with tuberculous pericarditis - Shenje, Justin Tapiwa; Raubenheimer, Peter; Wiesner, Lubbe; Ross, Ian (Frontiers in Endocrinology, 2023)
Pulmonary tuberculosis is an inflammatory disease associated with an elevated cortisol/cortisone ratio at the site of infection and an array of cytokine changes. Tuberculous pericarditis is a less common but more lethal form of tuberculosis and has a similar inflammatory process in the pericardium. As the pericardium is largely inaccessible, the effect of tuberculous pericarditis on pericardial glucocorticoids is largely unknown. We wished to describe pericardial cortisolcortisone ratio in relation to plasma and saliva cortisol/cortisone ratios and the associated changes in cytokine concentrations. The median (interquartile range) of plasma, pericardial, and saliva cortisol concentration was 443 (379–532), 303 (257–384), and 20 (10–32) nmol/L, respectively, whereas the median (interquartile range) of plasma, pericardial, and saliva cortisone concentrations was 49 (35–57), 15.0 (0.0–21.7), and 37 (25–55) nmol/L, respectively. The cortisol/cortisone ratio was highest in pericardium with median (interquartile range) of 20 (13–445), followed by plasma of 9.1 (7.4–12.1) and saliva of 0.4 (0.3–0.8). The elevated cortisol/cortisone ratio was associated with elevated pericardial, interferon gamma, tumor necrosis factor–alpha, interleukin-6, interleukin-8, and induced protein 10. Administration of a single dose of 120 mg of prednisolone was associated with the suppression of pericardial cortisol and cortisone within 24 h of administration. The cortisol/cortisone ratio was highest at the site of infection, in this case, the pericardium. The elevated ratio was associated with a differential cytokine response. The observed pericardial cortisol suppression suggests that 120 mg of prednisolone was sufficient to evoke an immunomodulatory effect in the pericardium.